1989
DOI: 10.1007/bf02535161
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil prevents change in arachidonic acid and cholesterol content in rat caused by dietary cholesterol

Abstract: Rats were fed diets high in either saturated fat (beef tallow) or alpha-linolenic acid (linseed oil) or eicosapentaenoic and docosahexaenoic acids (fish oil) with or without 2% cholesterol supplementation. Consumption of linseed oil and fish oil diets for 28 days lowered arachidonic acid content of plasma, liver and heart phospholipids. Addition of 2% cholesterol to diets containing beef tallow or linseed oil lowered 20:4 omega 6 levels but failed to reduce 20:4 omega 6 levels when fed in combination with fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 31 publications
1
5
1
Order By: Relevance
“…The mean body mass increased by 213+7 g in the control, 236±10 g in the n-6 treatment group, and 191 ± 12 g in the n-3 diet group. A similar observation of comparatively lower body mass in a dietary fish oil group was reported previously [15].…”
Section: Food Consumption and Body Weightssupporting
confidence: 89%
“…The mean body mass increased by 213+7 g in the control, 236±10 g in the n-6 treatment group, and 191 ± 12 g in the n-3 diet group. A similar observation of comparatively lower body mass in a dietary fish oil group was reported previously [15].…”
Section: Food Consumption and Body Weightssupporting
confidence: 89%
“…Using linseed oil [5] or perilla oil [6,7] as the sources of α-18 : 3, it has been reported that dietary α-18 : 3 in relation to both saturated fatty acids and 18 : 2 reduces serum lipid concentrations in rats as currently confirmed. However, the mechanism(s) by which dietary α-18 : 3 reduces serum lipid concentrations is not clear.…”
Section: Discussionmentioning
confidence: 88%
“…Available information indicated that dietary fats rich in n-3 octadecatrienoic acid (α-linolenic acid) such as linseed [5] and perilla oils [6,7] compared to those rich in n-6 octadecadienoic acid (linoleic acid) decrease serum lipid concentrations in the rat. It is probable that dietary α-linolenic acid, as in the case of fish oil, modifies fatty acid metabolism in the liver and thus, decreases serum lipid concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Data on total cholesterol levels under HF diets are inconsistent, and definite statements about the putative induction of hypercholesterinemia by a pure HF diet, i.e., without addition of cholesterol, do not seem possible from the literature at present. The only exception is fish oil‐based diets; there, a hypocholesterolemic effect is clearly established (45, 46, 47, 48).…”
Section: General Metabolic Effects Of Hf Dietsmentioning
confidence: 99%